An independently tunable dual control system for RNAi complementation in Trypanosoma brucei - Raveen Armstrong; Matt J. Romprey; Henry M. Raughley; Stephanie B. Delzell; Matthew P. Frost; James Chambers; Grace G. Garman; David Anaguano; Michele M. Klingbeil (PLoS ONE, 2025)
Trypanosoma brucei is a tractable protist parasite for which many genetic tools have been developed to study novel biology. A striking feature of T. brucei is the catenated mitochondrial DNA network called the kinetoplast DNA (kDNA) that is essential for parasite survival and life cycle completion. Maintenance of kDNA requires three independently essential paralogs that have homology to bacterial DNA polymerase I (POLIB, POLIC and POLID). We previously demonstrated that POLIB has a divergent domain architecture that displayed enzymatic properties atypical for replicative DNA polymerases. To evaluate the functional domains required for kDNA replication in vivo , we pursued an RNAi complementation approach based on the widely used tetracycline (Tet) single inducer system. Tet induction of RNAi and complementation with wildtype POLIB (POLIBWT) resulted in a 93% knockdown of endogenous POLIB mRNA but insufficient ectopic POLIBWT expression. This incomplete rescue emphasized the need for a more versatile induction system that will allow independent, tunable, and temporal regulation of gene expression. Hence, we adapted a dual control vanillic acid (Van)-Tet system that can independently control gene expression for robust RNAi complementation. Dual induction with Van and Tet (RNAi + Overexpression) resulted in 91% endogenous POLIB knockdown accompanied by robust and sustained ectopic expression of POLIBWT, and a near complete rescue of the POLIB RNAi defects. To more precisely quantify changes in kDNA size during RNAi, we also developed a semi-automated 3D image analysis tool to measure kDNA volume. Here we provide proof of principle for a dual inducer system that allows more flexible control of gene expression to perform RNAi and overexpression independently or concurrently within a single cell line. This system overcomes limitations of the single inducer system and can be valuable for elegant mechanistic studies in the field.